New Record of Arbuscular Mycorrhizal Fungi (AMF) Association with Kebar Grass (Biophytum petersianum Klotzsch.) in the Grassland Area of Kebar, Tambrauw Regency, West Papua, Indonesia - Irma Rahayu; Rosye H. R. Tanjung; Supeni Sufaati; Suharno Suharno (Journal of Tropical Biodiversity and Biotechnology, 2022)
Arbuscular mycorrhizal fungi (AMF) are an important form of symbiosis between fungi and plants in an ecosystem. One of the medicinal plants used by the people in West Papua is kebar grass (Biophytum petersianum Klotzsch.). This study aims to determine the AMF association in the rhizosphere of B. petersianum in grasslands. Survey method was used in this study. The presence of AMF was observed by examining root colonization and spore diversity. The results showed that the percentage of AMF colonization in roots was between 46.7–90.0% with an average of 71.66%. Meanwhile, the number of spores found in the plant rhizosphere averaged 119.8 spores per 10 grams of soil sample. There were 18 species of AMF dominated by the genus Glomus (7 species), Acaulospora (3 species), while the genus Claroideoglomus, Entrophospora, Gigaspora, and Scutellospora were dominated each with 2 species. This finding is the first record on the presence of AMF on B. petersianum in West Papua.